Effectiveness of HRIS Personnel Records Management on Performance of Higher Learning Institutions: A Case of Tengeru Institute of Community Development - R., Sikira; A., Mishael (International Journal of Scientific Research and Management (IJSRM), 2024)
Organisations recognise that human resource information systems improve HR efficiency and, hence, organisational effectiveness. This has increased the adaptability of these systems, but methods of quantifying their efficiency are challenging. Given the time and expense associated with HRIS deployment, organisations must justify this commitment. Therefore, this study sought to assess the effectiveness of HRIS personnel records management on the performance of higher learning institutions, in the case of the Tengeru Institute of Community Development. The researchers employed a descriptive research design in the course of conducting the research. The population of this research consisted of all employees of all departments of TICD. The researchers used simple random sampling to select respondents. Both primary data and secondary data were collected for the study. Data were analysed using descriptive and inferential statistics with SPSS version 26.0. Findings revealed a significant relationship between HRIS personnel records and TICD performance. The majority of respondents agreed that human information systems (HRIS) can track employee movement and improve information dissemination. HRIS is effective in meeting strategic goals and enabling employees to meet expectations. Implementation has reduced work duplication and improved employee performance. HRIS personnel records management is useful for keeping correspondence records and maintaining leave records. The composite mean of 3.5 indicates that HRIS personnel records management significantly affects the performance of TICD. The study recommends that the Tanzanian government should integrate Human Resource Information Systems (HRIS) into its all-HR management processes to enhance operational effectiveness, reduce work duplication, and improve personnel records management. Investing in employee training and change management strategies will maximise HRIS benefits and enhance organisational performance.